HIV/AIDS: Raising Minority Community Awareness - Eboni J. Baugh; Camille Callendar (EDIS, 2009)
FCS-8874, a 4-page fact sheet by Eboni J. Baugh and Camille Callendar, describes strategies for raising awareness of HIV/AIDS in minority communities. Includes links to effective prevention programs and references. Published by the UF Department of Family Youth and Community Sciences, March 2009.